Teachers’ Understanding and Practices on The Applications of 21st Century Learning in Secondary School Mathematics in Miri, Sarawak - Rakwi, Nur Shafiqah Hanim; Shafie, Sabarina; Syed Ali, Sharifah Aishah (Jurnal Pendidikan Bitara UPSI, 2021)
The objective of this research is to study the understanding and practices of Mathematics teachers on the application of 21st century learning in high schools in Miri, Sarawak. By using a quantitative approach, a questionnaire instrument was constructed and adapted from previous studies that focused on Mathematics teachers in Miri secondary schools as a sample of this study. The research outcome showed that Mathematics teachers have a high level of knowledge in 21st century learning. The application of 21st century learning for cognitive aspect, affective and psychomotor is at a moderate-high level. The statistical analysis one-way ANOVA shows that teachers’ understanding of 21st century learning based on teacher’s age was found to be insignificant at the value of F (df = 3, 90) = 1.060, p> 0.05 while for teachers’ understanding of 21st century learning based on teachers’ experience in teaching Mathematics was also not significant at F (df = 4, 89) = 1.931, p> 0.05. In conclusion, Mathematics teachers in Miri secondary schools have a high level of knowledge of 21st century learning. The practices of 21st century learning by teachers in teaching Mathematics for cognitive, affective and psychomotor aspects are at a moderately high level. Although there are differences in the mean between the teachers’ age and experience in teaching Mathematics on teachers’ understanding towards 21st century learning, these differences cannot be used to generalize this entire study population as there is no significant difference between the two variables, on teachers’ understanding towards 21st century learning. The results of this study are expected to help the relevant parties to ensure that teachers are better prepared to deliver 21st Century teaching in the classroom.